Global learning opportunities within social innovation in health (GLOWS): A modified Delphi process to identify and pilot core competencies for learning - Emily Wallace; Yusha Tao; Ogechukwu B. Aribodor; Zixuan Zhu; Angelica Borbón; Beatrice Halpaap; Bertha M. Chakhame; Eunice C. Jacob; Fatema Ahmed; Joel Msafiri Francis; Komang G. Septiawan; Kovey Mawuli; et al. (PLoS ONE, 2026)
Background Social innovation in health refers to the community-engaged process that connects health improvement and social change. The aim of this study was to develop a consensus statement on core learning competencies in social innovation in health and pilot them as part of a participatory training workshop. Methods and findings A modified Delphi Process aggregating data from a scoping review, global open call, and participatory process was organized. Participants were recruited from low, middle, and high-income countries with a range of social innovation experiences. Statements focused on social innovation in health core competencies for learning. Consensus was determined using the RAND/UCLA Appropriateness method. After expressing interest in the project, 68 individuals received the survey. 46 participants completed the first survey, and 35 completed the second. All 28 statements reached consensus, and based on the results of this first survey, some statements were added, amended, and merged to reach 30 consensus statements in the second survey. Competencies were categorized into skills, mindsets, and knowledge. Twenty-five statements had a median Likert rating score of >8 indicating strong agreement. Some competencies reached higher levels of agreement. This included community engagement, which can leverage the collective knowledge and problem-solving abilities of a diverse group of individuals to tackle complex challenges; social entrepreneurship skills including business model knowledge, securing funding, team building, and knowledge of intersectional issues and health inequities. Twelve competencies were then piloted as eight one-hour online workshops, which assessed the feasibility of developing them through online open-access social innovation training sessions. Afterwards,137 participants completed a survey rating their competency on a scale from 1 (not competent) to 5 (very competent),most reported a significant 1-point improvement including in entrepreneurship and understanding intersectionality. Conclusion The results from this study will inform the development of a WHO/TDR conceptual framework which will have implications for training program design and policy.